Survival and yield of the plantain Ebang (Musa spp., AAB genome, False Horn) produced from corm fragment initiated plants and suckers after hot water treatment in Southern Cameroon - Mekoa, C.; Hauser, S. (International Society for Horticultural Science, 2010)
Plantain (Musa spp.) is the most important food cash crop in SouthernCameroon. Farmers suffer severe income losses through yield losses due to pest anddisease infestation of suckers planted without any measure taken to remove pestsand diseases. This paper reports on the first trial conducted under farmers’condition on the performance of hot water treated suckers versus plants producedfrom corm fragments (CFP). Both techniques serve the purpose of planting pest(mainly nematode) and disease free propagules. Plantains were monitored for 50months after planting. Preflowering losses, mainly to death for unidentified reasonswere highest in CFP material. Uprooting and pseudostem break were not differentbetween CFP material and hot water and untreated suckers. Mean bunch mass washighest in CFP material. Due to the high plant losses of CFP material, bunch yield ofthe plant crop was lower than when conventional suckers were hot water treated.CFP material yield did not differ from that of traditionally prepared suckers. Rootnumber and root health in CFP plants were better than in both sucker treatments.None of these advantages was carried over to the first ratoon crop. CFP plants havea high potential to increase yields yet the weakness of high plant losses in thejuvenile phase needs to be overcome to make the technique adoptable.